Latvian /v/ and /ʝ/: acoustic study of different realizations - Grigorjevs, Juris; Indričāne, Inese; Taperte, Jana (Baltistica, 2016)
The goal of the current study is to register the distribution of different realizations of Latvian consonant phonemes /v/ and /ʝ/ in speech material consisting of symmetric CVC units in carrier phrases. For the acoustic analysis, three acoustic characteristics are used: spectral shape and relative intensity of the consonants in question, as well as relative duration of the formant transitions of context vowels.According to the results, fricative is the dominant allophone of /v/ both in prevocalic and postvocalic position, while for /ʝ/, it is fricative in the prevocalic position and vowel or approximant in the postvocalic position. Fricatives generally have higher spectral peak frequencies and larger frequency range in comparison with 314 approximants. Relative intensity values decrease from vowel to approximant and to fricative, and fricatives have the most variable relative intensity values. There are similar tendencies in the relative formant transition length for both /v/ and /ʝ/ – it is shorter for fricatives than for approximants and vowels.
Keywords: Standard Latvian; acoustic phonetics; fricative; approximant; spectral shape; relative intensity; relative duration of the formant transitions